2020
DOI: 10.4142/jvs.2020.21.e80
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effects of Bovine antimicrobial peptide against TGEV in vivo and in vitro

Abstract: Background: In suckling piglets, transmissible gastroenteritis virus (TGEV) causes lethal diarrhea accompanied by high infection and mortality rates, leading to considerable economic losses. This study explored methods of preventing or inhibiting their production. Bovine antimicrobial peptide-13 (APB-13) has antibacterial, antiviral, and immune functions. Objectives: This study analyzed the efficacy of APB-13 against TGEV through in vivo and in vitro experiments. Methods: The effects of APB-13 toxicity and vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“… Daneshmand et al (2020) investigated the effect of the addition of the antimicrobial peptide cLFchimera (20 mg/kg) to the diet of broiler chickens in the context of necrotic enteritis (NE) challenge and found that cLFchimera ameliorated intestinal lesions and changes to the villus morphology in the jejunum. Liang et al (2020) found that bovine antimicrobial peptide-13 (APB-13) had good antiviral activity against transmissible gastroenteritis virus (TGEV) and significantly reduced the piglet diarrhea induced by TGEV, thereby improving the intestinal villus morphology. Previous studies demonstrated that the antimicrobial peptide MccJ25 could protect against enterotoxigenic E. coli (ETEC) infection and significantly alleviate the destruction of intestinal morphology and changes in villus morphology in mice infected with ETEC ( Ding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… Daneshmand et al (2020) investigated the effect of the addition of the antimicrobial peptide cLFchimera (20 mg/kg) to the diet of broiler chickens in the context of necrotic enteritis (NE) challenge and found that cLFchimera ameliorated intestinal lesions and changes to the villus morphology in the jejunum. Liang et al (2020) found that bovine antimicrobial peptide-13 (APB-13) had good antiviral activity against transmissible gastroenteritis virus (TGEV) and significantly reduced the piglet diarrhea induced by TGEV, thereby improving the intestinal villus morphology. Previous studies demonstrated that the antimicrobial peptide MccJ25 could protect against enterotoxigenic E. coli (ETEC) infection and significantly alleviate the destruction of intestinal morphology and changes in villus morphology in mice infected with ETEC ( Ding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the antibacterial activity, AMPs also have a broad-spectrum antiviral activity against the enveloped viruses. For example, bovine antimicrobial peptide-13 effectively inhibits the viral proliferation by disruption of the viral protein synthesis and the viral gene expression in transmissible gastroenteritis virus [ 181 ]. The anti-herpes simplex virus (HSV) activity of AMPs, such as protegrin and indolicidin, have been attributed to blocking the adhesion and entry of the virus by targeting the viral membrane glycoprotein [ 182 , 183 ].…”
Section: Activity Of Ampsmentioning
confidence: 99%
“…Such dataset of 130 peptides is further utilized while training GAN. The peptides taken from literature and clinical trials are listed in following references - HIV candidates (Liang et al , 2020; Shi et al , 2016; Chupradit et al , 2017; Coffey et al , 1997); SARS COV (Xia et al , 2020); MERS (Zhao et al , 2016);T20 (Ding et al , 2017);Hepatitis B (Lempp et al , 2016);…”
Section: Methodsmentioning
confidence: 99%